Household environment and behavioral determinants of respiratory tract infection in infants and young children in northern bangladesh. Issue 6 (20th May 2015) - Nasanen‐Gilmore, S. Pieta K.; Saha, Subir; Rasul, Izaz; Rousham, Emily K.; Gurri, Francisco D.; Ortega‐Muñoz, Allan
<x xml:space="preserve">Abstract</x> Objectives Respiratory tract infections (RTI) are one of the leading causes of under‐five mortality in Bangladesh. Solid biomass fuels are the main source of domestic fuel used for cooking across Bangladesh, leading to smoke and pollution exposure in the home. This article aims to identify risk factors for RTI among children aged under five years in Bangladesh with a particular focus on the household environment, fuel use, and cooking practices. Methods A cross‐sectional household‐health survey was carried out in 321 households in northern Bangladesh. The survey included care‐giver interviews on cooking practices, child health, and household behaviors during cooking. Health status of the youngest child (under five years) from each household was recorded through maternal interviews, medical diagnosis, and assessment of biomarkers (C‐reactive protein (CRP), hemoglobin) from finger‐prick blood samples. Anthropometric status (weight, height) was recorded. Results Children who spent ≥30 minutes/day within 5 feet of the stove during cooking had a significantly increased risk of moderate/severe RTI compared with children spending <30 minutes/day close to the stove (OR = 2.15, 95%CI: 1.20–3.86, P = 0.01), independent of socio‐economic status (SES), biomass fuel type (wood, dung, plant‐derived, compressed rice husks), child age, anthropometric status, CRP and hemoglobin. Conclusions In environments with a heavy reliance on solid biomass fuels, the amount of time a child spends near the stove during cooking may be an important risk for RTI. These novel findings from Bangladesh warrant further investigation of mother‐infant behaviors during cooking in relation to child health, to ascertain whether the association is likely to be causal. Am. J. Hum. Biol. 27:851–858, 2015. © 2015 Wiley Periodicals, Inc.